Knowledge, Attitude, and Practice Regarding Colostomy Care Among Nurses at a Tertiary Level Hospital in Jhapa, Nepal: A Cross Sectional Study - Neupane, Pushpa; Karki, Pratima; Tamang, Chandani; Bista, Nagina; Dahal, Sushmita (Medical Journal of Eastern Nepal, 2026)
BackgroundColostomy care is essential for preventing complications and improving the quality of life of patients with intestinal stomas. Nurses play a key role in providing this care; however, gaps in knowledge, clinical skills& attitude may affect patient outcomes.ObjectivesTo assess the knowledge, attitude, and practice (KAP) of nurses regarding colostomy care in two hospitals of Eastern Nepal.MethodsA descriptive cross-sectional study was conducted among 116 registered nurses selected through convenience sampling. Data were collected using a structured self-administered questionnaire adapted from previously validated tools. Descriptive statistics were used to analyze the data in SPSS version 25. Ethical approval and informed consent were obtained.Results Most nurses demonstrated average knowledge, with 57.76% scoring within the average range and 36.21% showing good knowledge. However, item-specific performance revealed gaps in applied knowledge, especially in identifying the common type of colostomy (14.66%) and dietary management (27.59%). Practice scores showed that 52.59% had average practice, while only 28.45% demonstrated good practice. Procedural competencies Correct timing of pouch emptying (16.38%) and proper peristomal skin care (25.86%) were notably low. In contrast, attitudes were largely positive, with a mean attitude score of 42.10 ± 4.14, and 99.13% of nurses agreed that training in colostomy care is necessaryConclusionsNurses exhibited positive attitudes toward colostomy care but demonstrated only moderate knowledge and suboptimal practical skills. The discrepancy between confidence and competence highlights the need for structured, hands-on training and continuous professional development. Strengthening clinical education and skill-based workshops is recommended to enhance the quality of colostomy care and patient outcomes.